PENGARUH GREEN ACCOUNTING, ENVIRONMENTAL PERFORMANCE, DAN CARBON EMISSION DISCLOSURE TERHADAP PROFITABILITAS - Dwi Wulandari, Natalia; Haryati, Tantina (JURNAL AKUNTANSI FINANCIAL STIE SULTAN AGUNG, 2025)
This study aims to examine the extent to which the implementation of environmental accounting (green accounting), environmental performance, and transparency in carbon emission disclosure affect the profitability of energy sector companies listed on the Indonesia Stock Exchange (IDX) during the period from 2019 to 2023. A quantitative approach was used, utilizing secondary data obtained from the official IDX website and the official websites of the respective companies. Sample selection was carried out using purposive sampling based on predetermined criteria. Data analysis was conducted using panel data regression with the statistical software EViews version 12. The empirical results indicate that the implementation of green accounting practices and a high level of transparency in carbon emission disclosure have a positive and significant effect on company profitability, as measured by Return on Assets (ROA). Conversely, environmental performance on its own does not show a statistically significant effect. These findings suggest that the integration of environmental accounting is an effective mechanism for improving financial performance, whereas improvements in environmental performance and carbon emissions without aligned reporting and accountability may not directly impact the profitability of energy companies in Indonesia. Keywords: Green Accounting, Environmental Performance, Carbon Emission Disclosure, profitability